Bobby Fischer against the world [videorecording(DVD)] - Kennedy, Rory; Buchthal, Stanley F.; Justus, Matthew (Docurama Films : Distributed in the U.S. by New Video, 2011)
In the '70s, Chess was a Cold War sport. Since the end of WWII, the U.S. and the U.S.S.R. had been locked in mortal combat for supremacy of just about everything, and Bobby Fischer was America's hope. Chess prodigies aren't that rare, but Bobby Fischer made chess sexy, an almost impossible task. He captured the world's imagination, and he proved that the U.S. could produce a champion in a game where the winners always seemed to be Russians. Chess would seem to make a terrible spectator sport, but somehow this man ratcheted all of it up to new heights. Chess fans will find it short on details on what made his game unique, but most will find this a great portrait of a man who was so brilliant that it made him intensely unhappy. He couldn't handle his own genius, and in the end, that was what destroyed him. He wasn't a man against the world, but rather a man against himself. That was the one opponent he could never best.